Biodiesel production from moringa oleifera seeds using heterogeneous acid and alkali catalyst - Aqilah, Yahya (2013)
Due to the increasing energy demand and pollution problems caused by the use of fossil fuels, it has become necessary to develop alternative fuels as well as renewable sources of energy. The use of biodiesel as a substitute for conventional diesel has been of great interest. This is because biodiesel is biodegradable, non-toxic, renewable, and has low emission of carbon oxide, sulphur dioxide, particulates and hydrocarbons as compared to conventional diesel. Therefore, this study is conducted to investigate the possible production of biodiesel by using Moringa oleifera seeds oil through heterogeneous (acid and alkali) catalyst process. Moringa oleifera seeds oil can be used for biodiesel production by transesterification using calcium oxide (CaO) as an alkaline catalyst followed by esterification by using ferric sulphate catalyst. A sample of 50 mL oil was poured into the 3-neck round-bottom glass flask. Carefully, the methanol was poured into the oil with ratio 6:1, 12:1 and 18:1 for both alkali-catalyzed transesterification and acid-catalyzed esterification process. The catalyst concentrations, time reaction, agitation speed and the temperatures are fixed at 1wt%, 90 minutes, 200 rpm and 70 oC, respectively. As a result, the methyl esters (biodiesel) produced from Moringa oleifera seeds oil exhibits a high yield which is 48 mL (96%) and 45 mL (90%) for both alkali-catalyzed transesterification and acid-catalyzed esterification process by using methanol to oil ratio of 18:1, and catalyst concentrations, time reaction, agitation speed and the temperatures are fixed at 1wt%, 90 minutes, 200 rpm and 70 oC, respectively. As a conclusion, biodiesel can be produced from Moringa oleifera seeds oil as an alternative fuels as well as renewable sources of energy for future use